An exceptional prostate cancer case: Importance of cancer screening. Issue 1 (3rd June 2022) - Basaran, Elif; Kucukoztas, Nadire; Aktepe, Halit Oktay; Atak Tel, Burcin; Aktas, Gulali
Abstract: Prostate cancer is a common type of malignancy in male population. It may present with various clinical findings including urinary retention. Here, we present a prostate cancer case in an elderly man who investigated for the origin of long‐term fever and weight loss. A 69‐year‐old man presented to our institution for a fever lasting more than a month. He had no other signs of infection. He lost about 15 kg within 3 months. Total prostate‐specific antigen (PSA) measurement in serum and prostate biopsy revealed advanced prostate cancer. His complaints diminished with prostate cancer treatment. In conclusion, we suggest that prostate cancer should be kept in mind in the differential diagnosis of fever and weight loss in men over 50 years of age whether he is symptomatic or not.